Optimum Design of the Transmission of Mining Truck based on Maximum Actual Power - Zhang Guofen; Liu Zhaojie; Zhang Famin; Song Zhen (Jixie chuandong)
According to the design requirements and characters of mining truck,an optimum mathematical model of transmission is set up to maximize actual power under the precondition of reliability. The transmission of mining truck is optimized by using optimization toolbox of MATLAB. With the visual display of the optimum results,several performance indexes such as the driving force,stand-by power and actual power are compared with the original design and among the optimum model,thus can provide an alternative option. Compared with original design,a good optimization effect is obtained from the optimum model of transmission.